2008
DOI: 10.1257/aer.98.4.1605
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Economic Status and Child Health: Evidence from the United States

Abstract: Anne Case et al. (2002), using cross-sectional data, found a positive relationship between children's health and income, with income's protective effect increasing with age. Janet Currie and Mark Stabile (2003), using a panel of Canadian children, found that low- and high-SES children respond similarly to health shocks, but the low-SES children are subject to more shocks as they age. Our study examines this relationship using panel data for US children. We find some support for the latter result of Currie and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
100
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 11 publications
8
100
0
Order By: Relevance
“…Understanding the determinants of child health is important because health in childhood affects human capital accumulation, and health and labor market status in adulthood (Currie, 2008). Findings firmly establish that family income is positively related to children's general health in Australia (Khanam et al, 2009), Canada (Currie and Stabile, 2003), Germany (Reinhold and Jurges, 2011) and the US (Case et al, 2002;Condliffe and Link, 2008). Moreover, the correlation between family income and children's general health strengthens as children grow older in Canada and the US, meaning that the disadvantages associated with parental income accumulate as children age (Case et al, 2002;Currie and Stabile, 2003).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Understanding the determinants of child health is important because health in childhood affects human capital accumulation, and health and labor market status in adulthood (Currie, 2008). Findings firmly establish that family income is positively related to children's general health in Australia (Khanam et al, 2009), Canada (Currie and Stabile, 2003), Germany (Reinhold and Jurges, 2011) and the US (Case et al, 2002;Condliffe and Link, 2008). Moreover, the correlation between family income and children's general health strengthens as children grow older in Canada and the US, meaning that the disadvantages associated with parental income accumulate as children age (Case et al, 2002;Currie and Stabile, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…Currie and Stabile (2003) and Condliffe and Link (2008), we can exploit the longitudinal nature of the FACS data to examine the effect of income on the emergence of new specific problems and the effect of past specific problems on current general health, using dynamic models. However, the implementation of these models implies a decrease in the sample size (less than 51,000 observations).…”
Section: The Role Of Specific Health Problemsmentioning
confidence: 99%
“…For example, Currie and Stabile (2003) found that the income-health gradient among Canadian children is robust despite access to universal health coverage. Condliffe and Link (2008) explored the determinants of gradient steepening, including health shocks or cumulation of disadvantage as children age. Murasko (2008) attempted to differentiate the influence of permanent from current income, and Khanama et al (2009) studied the extent to which factors such as parental health and education reduce the income gradient among children.…”
mentioning
confidence: 99%
“…The one study (Condliffe and Link 2008) that uses the PSID has two observations on child health but does not make use of the fuller data on family income. Murasko (2008) does explore a few dimensions of income including hot deck imputations for missing income, the use of income from one year rather than a 2 year average and the use of wage income in place of family income.…”
mentioning
confidence: 99%